Belief reasoning model for mapping public participation in transport planning - Kronprasert,N. (Springer Verlag, 2015)
© Springer International Publishing Switzerland 2014. Public inquiry plays an essential role in the planning process of transport investment and improvement projects. It helps to ensure that decisions are made to achieve project’s goals and meet public needs. In public inquiries of transport planning process, policy-makers engage in dialogue in which the reasonableness and beliefs in their judgments are often questioned. Different stakeholders reason and provide evidence in support of their preferences, but these opinions are normally conflicting and ambiguous. This ambiguity is usually expressed as a “I don’t know” opinion, but ignored in the analyses. This paper proposes a belief reasoning model as a goal-oriented decision-making method for finding a transport alternative that best achieves the project’s goals. The proposed method is applied to evaluate a real-world public transport alternatives analysis. The proposed method provides a means for the planners and citizens to present their own logic and justifications during the public inquiry process.